In vitro study of the morphology of internal lower second molars - Humberto Ramah Menezes de Matos; Luanni Belmino Mastroianni; Aldo Angelim Dias (Revista Sul-Brasileira de Odontologia, 2015)
The mandibular molars are a group of teeth that have a complex internal morphology, and its fundamental knowledge is necessary. The second molar has two roots, one mesial and distal, but three canals are more commonly find: two in the mesial root and one in the distal root. Objective: To study through four criteria: radiographic, clinical, microscopic, and anatomy, the internal morphology of the mandibular second molars. Material and methods: This was a cross-sectional, in vitro, descriptive, observational study, in which 50 second molars were selected, having as exclusion criteria teeth destroyed by caries. Inclusion criteria comprised teeth with higid and semi-higid crowns Results: of mandibular second molars had three canals. The round-shaped cross section was the most common throughout the cervical-apical extension of both mesial (59%) and distal (47%) canals. However, other possible configurations and number of canals can be found in second molars, as the presence of four (12%) or five canals (3%). 36.7% of the mesial canals and 29.4% of distal canals were flattened in the mesial-distal direction and elongated in buccolingual direction; the variation of the "C-shaped" canal was found in 4% of cases. Conclusion: The most frequent configuration and number of canals of mandibular second molars were, respectively, the round-shaped cross section configuration in the entire length of the canal, and three canals. However the professional should be aware that this morphology may vary as shown in each research phase. Therefore, to achieve clinical success, the professional should have the knowledge of the internal morphology of these teeth and their possible variations.